2022
DOI: 10.1136/jitc-2022-004584
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-loaded macrophages as new therapeutic target in cancer

Abstract: Macrophages are main players of the innate immune system. They show great heterogeneity and play diverse functions that include support to development, sustenance of tissue homeostasis and defense against infections. Dysfunctional macrophages have been described in multiple pathologies including cancer. Indeed tumor-associated macrophages (TAMs) are abundant in most tumors and sustain cancer growth, promote invasion and mediate immune evasion. Importantly, lipid metabolism influences macrophage activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…Generally, increased lipid accumulation in TAMs is positively associated with their differentiation and function, especially because FAO is responsible for the downstream transcriptional regulation of several genes pertinent to TAM activity ( 7 , 8 ). By extension, several studies have shown that lipid accumulation in TAMs corresponds with tumor progression in a variety of cancer types ( 28 ). In gastric cancer, lipid accumulation in TAMs resulted in the upregulated expression of phosphoinositide 3-kinase (PI3K) -γ, which induced M2-like polarization ( 29 ).…”
Section: Lipids and Lipid Oxidation In Immune Cellsmentioning
confidence: 99%
“…Generally, increased lipid accumulation in TAMs is positively associated with their differentiation and function, especially because FAO is responsible for the downstream transcriptional regulation of several genes pertinent to TAM activity ( 7 , 8 ). By extension, several studies have shown that lipid accumulation in TAMs corresponds with tumor progression in a variety of cancer types ( 28 ). In gastric cancer, lipid accumulation in TAMs resulted in the upregulated expression of phosphoinositide 3-kinase (PI3K) -γ, which induced M2-like polarization ( 29 ).…”
Section: Lipids and Lipid Oxidation In Immune Cellsmentioning
confidence: 99%
“…As they play key roles in tumor development, macrophages are considered to be therapeutic targets. [38,39] In the TME, TAMs mainly have M2-like tumor-promoting effects and participate in various malignant characteristics, including immunosuppression and metastasis. [39,40] We analyzed the levels of various immune cells in the tissues of smoking and non-smoking NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…ACOT9, which is abundant in monocytes, is an acyl-coenzyme A (CoA) thioesterase group that degrades acyl-CoA into CoA and fatty acids. Fat accumulation due to ACOT9 deficiency in tumor-associated macrophages may promote tumor growth and suppress immunity [ 28 ]. The four mRNAs proposed in this study may reflect the implications of in a host immune capacity and NLR as an immune-suppression effect of cancer, from the perspective of past studies related to immune cells.…”
Section: Discussionmentioning
confidence: 99%